PENGUATAN LEAN MANAGEMENT DALAM PROBLEMATIKA PENGAWASAN INDUSTRI HALAL DI PROVINSI ACEH - Razali, Ramadhan; Fuadi, Fuadi; Falahuddin, Falahuddin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2023)
Both SMEs and non-SMEs have seen a sharp rise in the number of business actors in recent years. Aceh Province noticed a rice in the number of business actors. CSR toward the local environmental has not been felt despite the growing number of business actors. This study’s objective is to critique the oversight given to the halal industry in an effort to prevent any further growth. A qualitative method with a phenomenological perspective was used in this investigation. The conclusions of this study are ; first, to maximize halal value, supervisionof the main ingredient supply chain needs to be carried out. Supervision can be done by using an external supervisor. Second, IKM business actors in Aceh Province have not implemented value stream mapping in their industry. Even though the application of VSM can minimize waste costs. Third, to minimize wastages costs, IKM actors should provide guidance to breeders and farmers. The existence of farmers or livestock breeders will cut wasteful costs, such as ordering costs, purchasing costs and carry costs. Fourth, to attract consumer and investor interest, according to researchers, business actors must carry out application revolutions, such as using blockchain as a database. The exixtence of blockchain can help business actors in supervising supply chains and even finances.